2019
DOI: 10.36902/sjesr-vol2-iss2-2019(66-80)
|View full text |Cite
|
Sign up to set email alerts
|

Role of Breast Cancer Awareness Advertising Educational Messages in Educating Women to Develop a Precautionary Behavior

Abstract: Abstract Breast cancer is a burning female health related issue and constantly increasing the threat for women around the globe. This study intends to analyze the power of an educational intervention in form of educational message on television to educate Pakistani women in order to improve their attitudes in adoption of precautionary behavior. The effects of these educational communication strategies are recorded by using the quantitative survey technique and a close ended questionnaire was distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The main source of information in the current study about breast cancer was through electronic media (37.5%), friends (20.8%), and health workers (34.1%). A study conducted in Pakistan revealed social and electronic media as a significant source of information about breast cancer and breast selfexamination [26] . The role of health professionals and electronic media would be pivotal in this context [27] .…”
Section: Discussionmentioning
confidence: 99%
“…The main source of information in the current study about breast cancer was through electronic media (37.5%), friends (20.8%), and health workers (34.1%). A study conducted in Pakistan revealed social and electronic media as a significant source of information about breast cancer and breast selfexamination [26] . The role of health professionals and electronic media would be pivotal in this context [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Media and its influence on how people evaluate think, and the act of citizenry towards climate change is a fertile area of research (Eurobarometer, 2009;Lorenzoni & Hulme, 2009;Ryghaug, Holtan Sørensen, & Naess, 2011;Wei, Zhu, Marinova, & Wang, 2017). In Pakistan, many studies have been conducted to examine the role of media in motivating people to adapt to pro-healthy behavior (Hingorjo & Memon, 2019;Iftikhar, Aziz, & Yousaf, 2019;Iftikhar & Mughal, 2017;Obregón et al, 2009;Raza et al, 2020). However, in Pakistan, media give marginal coverage to human development issues such as health, environment, and pollution (Kamboh & Yousaf, 2020).…”
Section: Role Of Media In Health Awarenessmentioning
confidence: 99%
“…Pakistani women between aged 20-40 years showed a significant relationship between detection of breast cancer. Advertising educational message that are being broadcasted by television during a specific period of time (Iftikhar, Aziz & Yousaf, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The aim of present study is determined at finding the awareness of breast cancer among women and precautionary measures of breast cancer in women and also measuring the behavioral intention of women after watching Public Service Awareness Messages about breast cancer. (Iftikhar, Aziz & Yousaf, 2019). Furthermore it is required to know the need of improvement in the health related advertisements, especially focuses on the major disease that is breast cancer because it became very common in society.…”
Section: Introductionmentioning
confidence: 99%